Hygrothermal Post-Buckling Analysis of Laminated Composite Beams - Akbaş, Şeref Doğuşcan (Imperial College Press, 2019)
The main goal in this paper is to make analysis of post-buckling of laminated composite beams under hygrothermal effect. In solution of problem, finite element method is utilized with the first shear beam theory. Total Lagrangian approach is used nonlinear kinematic relations. It is known that post-buckling problems are geometrically nonlinear problems. In nonlinear solution of problem, the Newton-Raphson method is used based on incremental displacement. The novelty in this study is to investigate the hygrothermal post-buckling analysis of laminated composite beams by using total Lagrangian nonlinear approach. The influences of temperature, moisture, fiber orientation angles, stacking sequence of laminas on post-buckling responses of composite laminated beam are illustrated and examined in numerical results. The results show that fiber orientation angles, stacking sequence of laminas play an important role in hygrothermal post-buckling responses of laminated beams. Also, comparison studies are performed with special results of published paper.
Keywords: Laminated composite beams; post-buckling; hygrothermal effect; finite element method; total lagrangian